Serum bilirubin levels in Turkish adults show inverse relation with insulin resistance and overall obesity, without association with metabolic syndrome - Onat, Altan; Ozhan, Hakan; Karabulut, Ahmet; Albayrak, Sinan; Can, Gunay; Hergenc, Gulay (TURKISH SOC CARDIOLOGY, 2007)
Objectives: We investigated serum bilirubin levels and their association with insulin resistance (IR), metabolic syndrome (MS) or its components, and coronary heart disease (CHD) among Turkish adults. Study design: Serum bilirubin concentrations were measured in 1,052 male and female participants of a representative cross-sectional Turkish cohort living in the Marmara and Middle Anatolia regions. Metabolic syndrome was defined by modified criteria of the Adult Treatment Panel III. Results: The median age of the cohort was 53 years. Metabolic syndrome was identified in 235 males (46%) and 253 females (46.8%). The mean serum bilirubin concentration was 0.59 +/- 0.34 mg/dl in males, and 0.53 +/- 0.34 mg/dl in females (p=0.004). Serum bilirubin levels showed significant positive correlations with serum protein, albumin, testosterone, age, diastolic blood pressure, creatinine, and folic acid, and inverse correlations with smoking, body mass index, and IR. Serum bilirubin was correlated with HDL-cholesterol only in males. Of these factors, obesity, IR (inversely), and diastolic blood pressure were the main independent covariates of serum bilirubin. Logistic regression analysis showed that IR was significantly associated with the bottom quartile of bilirubin (<= 0.34 mg/dl) (OR: 1.91; 95% CI: 1.14-3.18), with a stronger association only in females (OR: 2.43; 95% CI 1.21-4.88). Bilirubin levels were not in significant association with CHD and MS. Conclusion: Insulin resistance, but not MS components related with central obesity, was associated with low levels of serum bilirubin in Turkish adults. This relation is more prominent among females and supports the hypothesis that serum bilirubin possesses antioxidant function.
Keywords: Bilirubin/blood; coronary disease; insulin resistance; metabolic syndrome X; obesity; sex factors; Cardiovascular System & Cardiology